Querying texts with the AntConc corpus software - Rajeg, Gede Primahadi Wijaya; Laksminy, Luh Putu; Rajeg, I Made (LPPM Universitas Dhyana Pura, 2026)
AntConc is an open-source corpus linguistic tool featuring basic corpus linguistic analytical techniques. A powerful element of AntConc is its various pattern-searching methods. This paper describes the flavours of AntConc’s searching methods and illustrates them for the query of phonological, morphological, and syntactic phenomena. The more advanced searching method, namely Regular Expressions (RegEx), is also discussed. The paper illustrates the use of RegEx for querying a rather complex morphological phenomenon in Indonesian, namely reduplication. RegEx search output is compared with the output from the basic Wildcard search feature to accentuate the sophistication and flexibility of RegEx for more targeted and specific results. The paper, overall, underscores the importance of mastering the different methods of querying texts with different complexities in AntConc for investigating a wider range of data-intensive, linguistic inquiries.